Molecular Basis of the Slow Growth of Mycoplasma hominis on Different Energy Sources - Evsyutina, Daria V.; Semashko, Tatiana A.; Galyamina, Maria A.; Kovalchuk, Sergey I.; Ziganshin, Rustam H.; Ladygina, Valentina G.; Fisunov, Gleb Y.; Pobeguts, Olga V. (Frontiers in Cellular and Infection Microbiology, 2022)
Mycoplasma hominis is an opportunistic urogenital pathogen in vertebrates. It is a non-glycolytic species that produces energy via arginine degradation. Among genital mycoplasmas, M. hominis is the most commonly reported to play a role in systemic infections and can persist in the host for a long time. However, it is unclear how M. hominis proceeds under arginine limitation. The recent metabolic reconstruction of M. hominis has demonstrated its ability to catabolize deoxyribose phosphate to produce ATP. In this study, we cultivated M. hominis on two different energy sources (arginine and thymidine) and demonstrated the differences in growth rate, antibiotic sensitivity, and biofilm formation. Using label-free quantitative proteomics, we compared the proteome of M. hominis under these conditions. A total of 466 proteins were identified from M. hominis, representing approximately 85% of the predicted proteome, while the levels of 94 proteins changed significantly. As expected, we observed changes in the levels of metabolic enzymes. The energy source strongly affects the synthesis of enzymes related to RNA modifications and ribosome assembly. The translocation of lipoproteins and other membrane-associated proteins was also impaired. Our study, the first global characterization of the proteomic switching of M. hominis in arginine-deficiency media, illustrates energy source-dependent control of pathogenicity factors and can help to determine the mechanisms underlying the interaction between the growth rate and fitness of genome-reduced bacteria.